2022
DOI: 10.1016/j.irbm.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Laparoscopic Vision Improves Detection of Intraoperative Adverse Events During Laparoscopy

Abstract: Background: The absence of visibility of the entire surgical scene in laparoscopic surgery can lead to unforeseen intraoperative complications. An Enhanced Laparoscopy Vision System (ELViS) was developed to eliminate the blind spots of the traditional endoscope by providing a broad view of the surgical scene from a distance, thanks to two additional images. This study assessed whether the broad view provided by the Enhanced Laparoscopic Vision (ELV) helped the surgeon to detect and react to an unexpected intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In [ 6 ], a modified trocar with two miniature cameras was evaluated through animal experiments. Preliminary works have shown a reduction in operating time, in the number of commands of a robotic endoscope holder [ 7 ], and a faster reaction to adverse events [ 8 ] in a testbench environment. In [ 9 ], a trocar–camera assembly deployed four miniaturised cameras, increasing the FoV of a 10 mm endoscope by 51%.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 6 ], a modified trocar with two miniature cameras was evaluated through animal experiments. Preliminary works have shown a reduction in operating time, in the number of commands of a robotic endoscope holder [ 7 ], and a faster reaction to adverse events [ 8 ] in a testbench environment. In [ 9 ], a trocar–camera assembly deployed four miniaturised cameras, increasing the FoV of a 10 mm endoscope by 51%.…”
Section: Introductionmentioning
confidence: 99%
“…Augmented laparoscope solutions involve modifying existing laparoscope architectures with additional technology or devices, such as scanning prism assemblies 20 , 21 or panomorph lenses 22 , to expand the viewable area. Custom imaging trocars (CITs), like the Enhanced Laparoscopic Vision System 23 , 24 , feature cameras and lights that capture large FOVs to supplement or replace traditional laparoscopes. To facilitate insertion through the abdominal wall, most CITs exhibit mechanical mechanisms, such as sliding tacks or folding arms 23 28 , for remote intracorporeal deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Custom imaging trocars (CITs), like the Enhanced Laparoscopic Vision System 23 , 24 , feature cameras and lights that capture large FOVs to supplement or replace traditional laparoscopes. To facilitate insertion through the abdominal wall, most CITs exhibit mechanical mechanisms, such as sliding tacks or folding arms 23 28 , for remote intracorporeal deployment. Intracorporeal vision networks (IVNs) are comprised of one 29 or more 30 33 stand-alone imaging devices that are mounted or placed inside the abdominal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The User Interface and the characteristics of the ELViS were developed on a test bench to identify the optimal configuration. A preliminary study describing bench experiments was recently published [15]. The results showed that an adverse event could be detected earlier when using ELViS.…”
Section: Introductionmentioning
confidence: 99%